Classroom Behavior of Students With or At Risk of EBD: Student Gender Affects Teacher Ratings But Not Direct Observations. (February 2021) - Sheaffer, Amanda W.; Majeika, Caitlyn E.; Gilmour, Allison F.; Wehby, Joseph H.
As the field moves toward adaptive and individualized behavior intervention, it is important to identify and consider relevant student characteristics as potential levers (i.e., critical factors) for improving intervention effectiveness. Motivated by previous findings suggesting that behavioral profiles and teachers' perceptions of students with problem behavior vary by student gender, we evaluated gender differences in teacher ratings and direct observations of classroom problem behavior for elementary students with or at risk of emotional and behavioral disorder (EBD; N = 352). We found significant gender differences for teacher ratings of problem behavior, social skills, and academic competence. However, we did not find significant differences between male and female students on direct observation measures of behavior or reading skills. These findings provide evidence suggesting that student gender may be a critical factor in addressing classroom problem behavior. Future work in this area will help guide researchers and practitioners in considering how student gender and related teachers' perceptions may inform intervention selection and implementation for students with or at risk of EBD.